Conceptual ecology of evolution acceptance among Greek education students: the contribution of knowledge increase - Athanasiou, Kyriacos; Katakos, Efstratios; Papadopoulou, Penelope (J. Biol. Educ., 2012)
In this study, we explored the factors related to acceptance of evolutionary theory among students/preservice preschool education teachers using conceptual ecology for biological evolution as a theoretical frame. We aimed to examine the acceptance and understanding of evolutionary theory and also the relationship of acceptance and understanding of the nature of science, thinking dispositions and religiosity as independent variables. We also studied the influence of teaching on the conceptual ecology of evolution acceptance. A class of 320 future teachers was surveyed using two questionnaires. According to our findings, students' understanding of evolutionary theory is positively correlated with a moderate acceptance of evolutionary theory. We found a weak positive correlation between the understanding of the nature of science and acceptance of evolution theory, and a positive correlation between open-minded thinking dispositions and evolution theory acceptance. The strength and the patterns of these correlations are miscellaneous and are examined carefully in this paper. We also found that systematic teaching may have a significant influence on evolution theory acceptance. Our findings stress the differences that exist between societies and how socio-cultural factors such as type of religion influence acceptance of evolution and have a strong influence on evolution education.